2017
DOI: 10.1097/opx.0000000000001015
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging of Serpiginous Choroiditis

Abstract: Serpiginous choroiditis may manifest with multifocal lesions and may be confused with relentless placoid chorioretinitis. However, it ends up in a typical geographic scar. Optical coherence tomography can be used to monitor the changes in retinal structure. Choriocapillaris changes as seen on optical coherence tomographic angiography may be a possible mechanism behind the development of choroidal neovascularization in later stages of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…OCTA of choriocapillaris on active lesions shows clearly demarcated flow-deficit areas that correspond precisely to the hypofluorescent lesions on ICGA [82,83]. Conversely, inactive lesions demonstrate some detectable flow within the areas of flow void, indicating deeper medium-to-large choroidal vessels existence and choriocapillaris loss, better detected on OCTA than on ICGA [23,84,85].…”
Section: Punctate Inner Choroidopathymentioning
confidence: 83%
See 1 more Smart Citation
“…OCTA of choriocapillaris on active lesions shows clearly demarcated flow-deficit areas that correspond precisely to the hypofluorescent lesions on ICGA [82,83]. Conversely, inactive lesions demonstrate some detectable flow within the areas of flow void, indicating deeper medium-to-large choroidal vessels existence and choriocapillaris loss, better detected on OCTA than on ICGA [23,84,85].…”
Section: Punctate Inner Choroidopathymentioning
confidence: 83%
“…During the healing process, as a result of the choriocapillaris atrophy in some patients, medium-to-large choroidal vessels may be visualized in choriocapillaris zone on en face OCTA [89]. Vascular abnormalities, including nonneovascular tufts, tangled vessels and neovascular membranes may also be assessed with OCTA, which clearly demarcates the involvement of various retinochoroidal layers [85,89].…”
Section: Tuberculosismentioning
confidence: 99%
“…Khan and Shahzad14 reported a case of active lesions of SC showing loss of choriocapillaris homogeneity at OCT-A. Also, Ahn et al 15 have demonstrated decreased vascularity of the choriocapillaris in an active lesion using OCT-A.…”
Section: Discussionmentioning
confidence: 97%
“…Also, Ahn et al 15 have demonstrated decreased vascularity of the choriocapillaris in an active lesion using OCT-A. They hypothesised that the destruction of the choriocapillaris may lead to photoreceptor disruption, then to an important visual loss 14. See comment in PubMed Commons below.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there are only case reports concerning OCTA and one case series encompassing 3 patients in SC [15]. Therefore, the aim of this study is to describe these ndings in greater extent and compare them to known diagnostic tools, such as FA, ICGA, fundus auto uorescence (FAF), and enhanced depth imaging optical coherence tomography (EDI-OCT) [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%